The Correlation between Enviromental Knowledge and Enviromental Care Attitude on Biological Education Students in State University of Jakarta - Eka Putri Azrai; Maya Gayatri Widyasa; Ratna Komala (Program Studi Pendidikan Biologi Universitas Borneo Tarakan, 2023)
The environment plays an important role in human life. Knowledge of the environment can affect the attitude of caring for the environment. This study aims to determine the correlation between enviromental knowledge and enviromental care attitude students of Biology Education Study Program, UNJ. This research was conducted at State University of Jakarta on February 2022. The total samples used were 70 students, taken by Simple Random Sampling. The methode used is a quantitative method with a correlational study. Statistical hypothetis test through Linearity test and Pearson Correlation test. It is known that thera is a positive relationship between enviromental knowledge and enviromental care attitude with correlation coeficient in high category. The relationship that formed is a positive relationship, so the higher the student's environmental knowledge, the better the enviromental care attitude. Further research needs to be done in order to find other variables that are suspected to have a relationship to student’s knowledge of the environment with an enviromental care attitude so that student’s knowledge and student’s enviromental care attitude can be increased. The application of the good environmental care attitude of UNJ Biology Education students also needs to be appreciated by the University. With awards related to students' caring attitude towards the environment, it can bring up environmental care attitudes for other students.